COST RECOVERY ANALYSIS IN PRODUCTION SHARING CONTRACT IN UPSTREAM OIL AND GAS INDUSTRY (STUDY ON GAS UPSTREAM INDUSTRIES INDONESIA) - Arifin, Kasman; Hidayat, Dina (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to: 1) analyze empirically and test the effect of cost recovery in the Production Sharing Contract (Oil and Gas Production Sharing). 2) empirically analyze and test the effect of cost recovery in the upstream Oil and Gas Industry on State Revenues. The unit of analysis of this research is the upstream oil and gas industry managed by the Indonesian government with a Production Sharing Contract system with 44 companies or contract operator cooperatives. The population includes those who work as operators of cooperation contract contractors and SKK MIGAS with 62 manager levels, 51 professionals and 18 university researchers. And the researchers also used secondary data in SKK MIGAS in the 1984-20019 period. This research uses a qualitative approach, and the analysis of the data used is descriptive analysis, because the data analysis is done not to accept or reject hypotheses, but in the form of descriptions of observed symptoms, which are not always in the form of numbers or coefficients between variables . However, the emphasis is not on hypothesis testing, but on efforts to answer research questions through formal and argumentative ways. The results of the study indicate that there is a relation between the Cost Recovery component and the terminology in the Production Sharing Contract in the Upstream Oil and Gas Industry in Indonesia . By placing the right cost post on cost recovery will be able to reduce production costs from the Cooperation Contract Contractor (KKKS).